The Addictive Behavior of Judol, Pinjol, Loan Sharks and Their Impact on the Resilience of Muslim Families at Winong-Pati and Urban Genuk-Semarang, Central Java - A. Zaenurrosyid; Hidayatus Sholihah; Saifuddin; Abdelaali Maggouri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The spread of moneylenders (rentenir), online lending (pinjol), and online gambling (judol) in Central Java threatens the resilience of Muslim families both economically and through addictive behaviors. In rural areas such as Winong and several sub-districts in Pati, rentenir remain the primary source of financing for farmers and micro-entrepreneurs who are excluded from formal financial services, while judol proliferates through local networks and simple mobile devices. In contrast, in urban areas such as Genuk and several sub-districts in Semarang, pinjol has expanded rapidly due to digital penetration, lenient requirements, and aggressive promotion, typically used for urgent needs and non-productive consumption. Field data indicate that 38% of Muslim families in Pati have dealt with rentenir, 21% have engaged in judol, while 41% of Semarang families accessed pinjol in the past three years.This research uses a phenomenology approach, viewed from the perspective of maqasid sharia, covering two villages in Winong-Pati and two sub-districts in Genuuk -Semarang City Data were gathered through in-depth interviews with 24 informants—including household heads, spouses, religious leaders, and local officials—supplemented by participatory observation to capture family coping strategies under economic strain. Using Miles & Huberman’s interactive model, data analysis involved reduction, display, and conclusion drawing. Findings highlight two points. First, the practices of loan sharks, pinjol, and judol significantly undermine family resilience across economic stability, marital harmony, child-rearing quality, and socio-religious engagement. Second, although rural and urban contexts differ in forms of involvement, consequences converge on psychological distress, domestic conflict, weakened parenting, and declining social participation. These results underscore the relevance of maqasid al-shariah in protecting families from riba and gharar, reinforcing the ethical foundation of fiqh muamalah